Adam Watkins' 4th Grade Manchester-Gate Class Tour of Fresno Bee Facility at 1921 E Street, Fresno - Watkins, Howard::::::::: (1987)
Ron Orozco in the downstairs press room with the large rolls of paper used to print the Fresno Bee Students raising their hands in response to a question from Ron Orozco